Prevalence of periodontitis in adolescents: A systematic review protocol - Ana Beatriz de Oliveira Monteiro; Lia Rosana Honnef; Júlia Meller Dias de Oliveira; Patrícia Pauletto; Carla Massignan; Cristine Miron Stefani; Glaucia Santos Zimmermann; Graziela De Luca Canto (PLoS ONE, 2025)
Periodontitis is considered an inflammatory disease that affects the tooth’s supporting structures, resulting in its progressive destruction, which can lead to several problems, such as loss of teeth, bone reabsorption, and even exacerbation of chronic systemic diseases. Periodontitis is a common periodontal condition in the adult dentate population, affecting approximately 6 in 10 individuals. Among those affected, approximately 25% develop the most severe form of the disease. The prevalence of periodontitis in adolescents is not well established. Therefore, this study protocol of a systematic review that aims to answer the following research question: “What is the prevalence of periodontitis in adolescents?”. This systematic review will include observational studies reporting the prevalence of periodontitis in individuals aged from 13 to 18 years without comorbidities. A search will be conducted in the following databases: EMBASE, LILACS (via BVS), MEDLINE (via PubMed), and Web of Science. The gray literature will be consulted through Google Scholar and ProQuest. No language or time of publication restrictions will be applied. To determine which studies will be included, two independent reviewers will select the articles through a two-phase process. In the first phase, reviewers will assess the titles and abstracts, and, in the second phase, they will read the full texts using predefined eligibility criteria. Data collected will include author, study design, year of publication, country, sample size, sex, age, diagnostic methods, definition of periodontitis, reliability of criteria, examination protocol, case classification and prevalence rates. The risk of bias will be assessed according to the JBI Critical Appraisal Checklist for Studies Reporting Prevalence Data. Results will be synthesized into a narrative description and, if possible, a meta-analysis will be conducted. The systematic review methodology will enable a comprehensive and accurate analysis of the available evidence. Moreover, this approach may contribute to clinical decision-making, promoting the use of more appropriate and preventive treatments.